Exploration on speed behaviour at dual two-lane highway in urban area - Nur Azyyatul Shahira, Samsuri (2017)
Speed has significant consequence for environment and road safety. Travel at safe and reasonable speeds on highway promotes the nation productivity. This because of most highways and vehicle are designed and built for safe operation at speed travel. Speeding which known as exceeding speed limit or driving too fast condition include many factors such as driver’s behaviour, vehicle performance, roadway characteristic and speed zoning where a safe limit for certain road. Speeding also contributing factors in road accident but mostly the drivers recognise that speeding contributes to road accident but they themselves also drive exceeding speed limit. Therefore, this study is conducted to investigate the speed profile trends at dual two-lane carriageway in urban area and to identify the relationship between speed and volume. To achieve this, Jalan Gambang - Kuantan was chosen as study location. This study was conducted by using Pneumatic Road Tube as tools to collect the main data of speed and volume. Then the descriptive analysis and correlation coefficient forms the basis of testing the relationship between speed and volume. The result explained that the speed and volume were related with one another.